2022
DOI: 10.3390/md20120745
|View full text |Cite
|
Sign up to set email alerts
|

Functional Diversification of Oyster Big Defensins Generates Antimicrobial Specificity and Synergy against Members of the Microbiota

Abstract: Big defensins are two-domain antimicrobial peptides (AMPs) that have highly diversified in mollusks. Cg-BigDefs are expressed by immune cells in the oyster Crassostrea gigas, and their expression is dampened during the Pacific Oyster Mortality Syndrome (POMS), which evolves toward fatal bacteremia. We evaluated whether Cg-BigDefs contribute to the control of oyster-associated microbial communities. Two Cg-BigDefs that are representative of molecular diversity within the peptide family, namely Cg-BigDef1 and Cg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…This AMP-microbe specificity may also be found in other systems: in Hydra jellyfish, the AMP NDA-1 is uniquely effective against its microbiome associate Curvibacter in vitro , and Curvibacter specifically fails to colonize NDA-1-expressing tissues [ 42 ]. Oyster big Defensins similarly show drastically different inhibitory concentrations against specific microbiome-relevant bacteria [ 43 ]. Finally, a recent GWAS of Persian domestic cats found that a G49E polymorphism in the AMP Calprotectin was a major risk factor for development of ringworm fungal skin disease [ 44 ], suggesting that these highly specific and important peptide–microbe associations are not restricted to invertebrates.…”
Section: Specificity Of the Immune Response Is Accomplished By Effectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This AMP-microbe specificity may also be found in other systems: in Hydra jellyfish, the AMP NDA-1 is uniquely effective against its microbiome associate Curvibacter in vitro , and Curvibacter specifically fails to colonize NDA-1-expressing tissues [ 42 ]. Oyster big Defensins similarly show drastically different inhibitory concentrations against specific microbiome-relevant bacteria [ 43 ]. Finally, a recent GWAS of Persian domestic cats found that a G49E polymorphism in the AMP Calprotectin was a major risk factor for development of ringworm fungal skin disease [ 44 ], suggesting that these highly specific and important peptide–microbe associations are not restricted to invertebrates.…”
Section: Specificity Of the Immune Response Is Accomplished By Effectorsmentioning
confidence: 99%
“…15.5814 Gram-positive bacterium Cg-BigDef1 in vitro activity tested against ecological microbes De San Nicolas et al . [ 43 ] their table 1 cat Microsporum canis fungus calprotectin GWAS, polymorphism Myers et al . [ 44 ] paper topic human atopic dermatitis unknown cause, autoimmune DEFB1 GWAS, polymorphisms common across two studies Prado-Montes de Oca et al .…”
Section: Tackling Resistant Microbes Through the Lens Of Effector Spe...mentioning
confidence: 99%
“…Instead, most AMP families have expanded and diversified through gene duplication events followed by rapid molecular diversification [ 56 ], as a result of directional selection pressures [ 61 ]. This molecular diversity creates synergy and enlarges the spectrum of antimicrobial activities of oyster AMP families, particularly Cg- Defs and Cg- BigDefs [ 24 , 62 ]. Remarkably, the gene expansion and sequence diversification of Cg- BigDefs has also conferred specificity to members of this peptide family against bacteria belonging to the oyster microbiota [ 24 ].…”
Section: The Immune System Shapes the Microbiotamentioning
confidence: 99%
“…Bivalve microbiota may be manipulated to prevent disease in aquaculture [22]. A fine-tuned dialogue between oyster immunity and its microbiota was evidenced from early life to adult stages [23][24][25]. Recently a first insight into microbial community gene functions has been made accessible, either by shotgun metagenomics [11] or metatranscriptomics [26].…”
Section: Introductionmentioning
confidence: 99%
“…The growing research on microbiota added a new dimension to AMP research due to its connection with a variety of human diseases (Wang et al, 2023; Wehkamp et al, 2005). AMPs are important players that shape microbiota (de San et al, 2022; Pierre et al, 2023; Snelders et al, 2021). Remarkably, a Paneth cell peptide YY was able to selectively eliminate pathogenic hyphae but not the commensal yeast form of Candida albicans (Pierre et al, 2023).…”
Section: Introductionmentioning
confidence: 99%